The prospects for biogas integration with fuel cells in the United Kingdom - Torija,S; Castillo-Castillo,A; Brandon,NP (Fuel Cells, 2015)
Anaerobic digestion (AD) presence is emerging in the UK because it has numerous environmental benefits as a waste management strategy and produces valuable biogas. This work shows that up to 5.5% of UK primary energy could be met by biogas, representing 14.4% of gas consumption. Fuel cells (FCs) are the most efficient and environmentally benign energy convertor of any device of equivalent scale and in addition are well suited for biogas utilization, which has worldwide led to the emergence of numerous integrated commercial applications. Thus, biogas coupling with fuel cells is proposed as a unique and virtuous AD scheme. A techno-economic model has been developed for the two types of AD plants with the highest development prospects in the UK, namely livestock and food waste plants, whose performance and feasibility at different scales are scrutinized under several policy scenarios, some of which incorporate supportive mechanisms for the introduction of FCs. Results confirm that conventional AD projects can already be profitable in the current market environment, while projects involving FCs proved environmentally superior, virtually suppressing harmful pollutant emissions and decreasing the CO2 emissions from using grid electricity and natural gas, at a reasonable avoided carbon cost in the best suited cases.